Bang-lish sentiment classification using deep learning - Saleheen, Abrar; Siam, Saleh Ahmed; Akter, Sanjeda; Ghosh, Akash; Ahona, Adiba Anbar (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.